Performance of older adults under dual task during stair descent - Cui Zhang; Wei Sun; Qipeng Song; Houxin Gu; Dewei Mao (Elsevier, 2018)
Background: Stair walking, especially in dual-task conditions, is a challenging daily routine for older adults. The purpose of this study is to investigate gait and postural control and explore the possible reasons for the fall risk encountered by healthy older adults under dual-task conditions during stair descent. Methods: Thirty healthy older female adults (aged 67 ± 1 years, standing height of 1.64 ± 0.17 m, body mass of 66.01 ± 4.27 kg, and education of 8.92 ± 0.95 years) were randomly recruited from local communities and instructed to perform stair descent in a step-by-step manner on a standardized staircase under single-task (stair descent) and dual-task (stair descent with subtraction in series of three) conditions. Multivariate analysis of variance with repeated measures was performed to test the significance of multiple comparisons of kinematic variables in the single- and dual-task conditions. A paired t-test with Bonferroni adjustment was performed when a significant difference was detected. Results: Gait speed, foot clearance, and hip flexion angle at the cross of the support leg decreased considerably, and step width increased remarkably among the healthy older adults under the dual-task condition relative to the situation in the single-task condition during stair descent. Conclusion: The gait performance and posture control of the healthy older female adults were disturbed by the second cognitive task. These adults implemented a compensation strategy to enhance their body stability under the dual-task condition during stair descent. Keywords: Activity of daily living (ADL), Cognitive task, Downstairs, Gait, Posture control